PERBANDINGAN SEDIAAN BASAH DENGAN SEDIAAN GRAM HAPUSAN SEKRET VAGINA UNTUK DIAGNOSIS BACTERIAL VAGINOSIS - P B Notopoero; Prihatini Prihatini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2006)
Bacterial vaginosis (BV) is a clinical condition with changes in the vaginal ecosystem. Under normal conditions, the vaginalecosystem contains Lactobacilli microflora but in BV condition, it contains mixed microflora ie combination of anaerobic bacteria andGardnerella sp. There are approximately 300 cases of BV a year in the Dr. Soetomo General Hospital. We can examine vaginal fluidmicroscopically to diagnose BV with wet mount and Gram stain method. Wet mount method is fast to do that clinicians can establishthe diagnosis and therapy earlier. Gram stain method is the gold standard method and more common to do in the laboratory but thestaining method can affect the result. This study aims to know the diagnostic value of wet mount method compared with Gram stainmethod for BV. There were 30 subjects from the Gynaecology Outpatient Clinic in the Dr. Soetomo General Hospital. They presentedwith from the leucorrhoea and fullfiled the clinical criteria for BV. We took the vaginal fluid and examined them with wet mount andGram stain microscopy. The percentage of agreement between wet mount and Gram stain method for BV Grade I is 66%, BV grade IIis 66%, BV grade III is 84.6%, and BV grade IV is 100%. The sensitivity of wet mount method is 85.71%, the specificity is 88.88%, thepositive predictive value and negative predictive value are 94.73% and 72.72%. Based on these data, wet mount method can replaceGram stain method to diagnose BV microscopically in the case that there is not enough time and resource for Gram stain. The wet mountmethod has good sensitivity, specificity, positive and negative predictive value. Wet mount method has a shortcoming in identifying themicroorganism, but this problem can be solved by combining this method with Gram stain method.